2012
DOI: 10.1039/c2cp23247b
|View full text |Cite
|
Sign up to set email alerts
|

Anion photoelectron spectroscopy of germanium and tin clusters containing a transition- or lanthanide-metal atom; MGen− (n = 8–20) and MSnn− (n = 15–17) (M = Sc–V, Y–Nb, and Lu–Ta)

Abstract: The electronic properties of germanium and tin clusters containing a transition- or lanthanide-metal atom from group 3, 4, or 5, MGe(n) (M = Sc, Ti, V, Y, Zr, Nb, Lu, Hf, and Ta) and MSn(n) (M = Sc, Ti, Y. Zr, and Hf), were investigated by anion photoelectron spectroscopy at 213 nm. In the case of the group 3 elements Sc, Y, and Lu, the threshold energy of electron detachment of MGe(n)(-) exhibits local maxima at n = 10 and 16, while in the case of the group 4 elements Ti, Zr, and Hf, it exhibits a local minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
142
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(174 citation statements)
references
References 70 publications
30
142
0
Order By: Relevance
“…11 −16 In particular, rare-gaslike M@Si 16 nanoclusters, such as neutral, anionic, and cationic Si 16 cages encapsulating metal atoms of group-4 (e.g., Ti@Si 16 and Zr@Si 16 ), group-3 (e.g., Sc@Si 16 − and Lu@Si 16 − ), and group-5 (e.g., V@Si 16 + and Ta@Si 16 + ), respectively, are selectively synthesized as magic number nanoclusters. They exhibit chemical and thermal stability, 11,12 which is important for creating functional materials via the hierarchical assembly of superatomic nanoclusters on solid surfaces without losing the original properties of each nanocluster.…”
Section: Introductionmentioning
confidence: 99%
“…11 −16 In particular, rare-gaslike M@Si 16 nanoclusters, such as neutral, anionic, and cationic Si 16 cages encapsulating metal atoms of group-4 (e.g., Ti@Si 16 and Zr@Si 16 ), group-3 (e.g., Sc@Si 16 − and Lu@Si 16 − ), and group-5 (e.g., V@Si 16 + and Ta@Si 16 + ), respectively, are selectively synthesized as magic number nanoclusters. They exhibit chemical and thermal stability, 11,12 which is important for creating functional materials via the hierarchical assembly of superatomic nanoclusters on solid surfaces without losing the original properties of each nanocluster.…”
Section: Introductionmentioning
confidence: 99%
“…Some theoretical and experimental studies suggested that the doping of transition metals (TMs) could improve the stabilization of the cage structures of germanium-based clusters and tailor their properties at the same time. [8,11,[27][28][29] Moreover, stable TM-doped germanium clusters may be used as building blocks for cluster-assembled materials. [4,5,30] It has been reported that cobalt-doped germanium nanomaterials have low resistivity, high thermal stability, and room temperature ferromagnetism; this results in potential applications in effective on-chip interconnects and nanoelectrodes for highly integrated nanoelectronic devices, spintronic devices, and field-emission displays.…”
Section: Introductionmentioning
confidence: 99%
“…The modern level of experimental methods does not allow us to obtain information on the geo metric structure of insulated clusters, while the theo retical methods often give contradictory results [3][4][5]. At the same time, the experimental investigation of the electron structure of the clusters is possible, and there are the publications in which the results of studying the electron energy spectrum of anion clusters by the method of photoelectron spectroscopy are presented [6][7][8]. However, no information on the structure of clusters detected in the experiment is contained in these publications; therefore, combining the results of computer simulation of stable structures with the results of photoelectron spectroscopy can become the effective method of determining the actual geometric structure of clusters.…”
Section: Introductionmentioning
confidence: 99%